PENGARUH MEDIA PEMBELAJARAN BERBASIS E-MAJALAH SEJARAH DALAM MENINGKATKAN KEMAMPUAN LITERASI DIGITAL SISWA KELAS XI SMA NEGERI 5 PEKANBARU - Muhammad Ridho Nursalam (Yayasan Nusantara Hasana Berdikari, 2025)
Education plays a crucial role in the progress of a nation. Through effective education, a nation can acquire new knowledge that can be used to develop superior human resources. One of the subjects that can bring about change and development in society, particularly for students, is History. Aspects of digital literacy skills include the ability to access (access skill), analyze (analyze skill), evaluate (evaluate skill), and participate (participate skill). This research is classified as quantitative research, using a quasi-experimental design. The results of this study indicate an effect of using e-magazine learning media in history subjects on the digital literacy of 11th-grade students at SMAN 5 Pekanbaru. Based on the hypothesis test conducted, the calculated t-value thitung was 7.270, while the critical t-value ttabel was 1.661. The comparison shows that thitung > ttabel 7.270 > 1.661), meaning that the alternative hypothesis Ha is accepted and the null hypothesis H0 is rejected. This signifies that the application of e-magazine learning media in history subjects has an impact on the digital literacy skills of 11th-grade students at SMAN 5 Pekanbaru.